Intrafascicular Injection of Ammonium Sulfate and Bupivacaine in Peripheral Nerves of Neonatal and Juvenile Rats. Issue 2 (March 1998) - Hertl, M. Catherine; Hagberg, Patricia K.; Hunter, Daniel A.; Mackinnon, Susan E.; Langer, Jacob C.
Abstract : Background and Objectives: Regional nerve blocks are often used for the treatment of postoperative pain in children. Ammonium sulfate is a non-narcotic anesthetic agent, which has been reported to provide pain relief lasting days to weeks, with few reported side effects in adult studies. Prior to considering clinical use in children, the neurotoxicity of ammonium sulfate in 4-day and 3-week old rats was assessed and compared with that of bupivacaine. Methods: Each rat received a posterior tibial nerve intrafascicular injection (0.01 mL in 4-day-old and 0.02 mL in 3-week-old rats) using either 10% ammonium sulfate (n = 24 per age group), 0.5% bupivacaine (n = 18 per age group), 0.9% saline (n = 18 per age group), or 5% phenol (n = 18 per age group). A functional assessment by serial walking track analysis and a morphologic assessment by neurohistology were made. Results: No abnormalities in serial walking track analysis and no structural nerve damage were detected after ammonium sulfate, bupivacaine, or saline injection. Bupivacaine caused mild focal changes in both age groups, which recovered by 8 weeks. Conclusions: Intrafascicular injection of ammonium sulfate was as safe as bupivacaine in this animal model. Further animal studies must be made before human trials are initiated.